2021
DOI: 10.51470/plantarchives.2021.v21.s1.249
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biological Silica in Enhancement of Agricultural Productivity : A Review

Abstract: Role of biological silica in enhancement of agricultural productivity : A Review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In sustainable crop production, the application of silicon has been increasing as a low input and environmentally friendly technique to stimulate plant growth and alleviate abiotic stresses [Kaur et al 2021, Malik et al 2021, Wang et al 2021]. Althought potato is a silicon low-accumulator, foliar silicon application may contribute to enhancing potato yield [Luz et al 2008, Soratto et al 2012, Vulavala et al 2016, Laane 2017, which was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In sustainable crop production, the application of silicon has been increasing as a low input and environmentally friendly technique to stimulate plant growth and alleviate abiotic stresses [Kaur et al 2021, Malik et al 2021, Wang et al 2021]. Althought potato is a silicon low-accumulator, foliar silicon application may contribute to enhancing potato yield [Luz et al 2008, Soratto et al 2012, Vulavala et al 2016, Laane 2017, which was confirmed in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…Since silicon plays an important role in regulating physiological and biochemical processes, it has a potential role in mitigating various environmental stresses. Silicon has been proven to play an important role in mitigating drought stress [Kaur et al 2021, Malik et al 2021, Wang et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Once converted to chitosan, the polymer becomes soluble in mildly acidic solution. 11 Glucosamine is water soluble and sold as a nutritional supplement. 12…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Once converted to chitosan, the polymer becomes soluble in mildly acidic solution. 11 Glucosamine is water soluble and sold as a nutritional supplement. 12 The superior ability of chitin to form high-strength biomaterials, 13 has directed research into finding solutions to convert native chitin into usable forms via top-down (dissolution or fibrillation) or bottom-up approaches (electrospinning of dissolved fibres).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of silicon are particularly distinct under environmental-stress conditions [3,5,6]. Since silicon plays an essential role in mitigating biotic and abiotic stresses (high temperature, freezing, drought, salt stress, disease and insect stress, and other stress factors) on plants [4,5,[7][8][9][10], the use of silicon as a biostimulant to improve plant growth under stress conditions and increase crop productivity has been increasing.…”
Section: Introductionmentioning
confidence: 99%